RELATIONSHIP BETWEEN JOB STRESS AND NURSE PERFORMANCE AT ABDUL MANAP JAMBI HOSPITAL IN 2022 - Darmawanto, Darmawanto; Mawarti, Indah; Rudini, Dini (Jurnal Keperawatan Universitas Jambi, 2024)
A nurse is someone who works in a hospital and plays an important role in the delivery of health services. The performance of nurses issomething that can be felt by patients, if poor performance it can have animpact on decreasing the quality of service. Job stress has a negative impact on performance, because stress becomes an adaptive response that is channeled by individual differences or psychological processes, which are a consequence of any actions from outside the situation, or events that impose excessive psychological or physical exertion on a person.This study uses survey method research with an explanatory research approach or explanatory research to explain the relationship between two or more variables, namely "explaining the relationship between work stress and the performance of nurses at Abdul Manap Hospital Jambi in 2021". The population in this study were nurses who served in the operating room and emergency room at Abdul Manap Hospital Jambi 2022. In this study, the sample was taken using the Proportional Stratified Random Sampling method which aims to ensure that the samples from each group member can be divided professionally so that it can be adequate. The results of this study indicate a significant p-value of 0.015 (<0.05) So the conclusion is that there is a relationship between work stress and the performance of nurses at Abdul Manap Hospital Jambi in 2022. It is recommended as input material in order to increase the benefits of adding reading material about work stress for health education institutions so that they can improve the quality of nursing for nurses and can apply nursing care properly and correctly.